The orchid collections and illustrations of Consul Friedrich C. Lehmann - Cribb, Phillip (Universidad de Costa Rica, 2010)
Paradise for an orchid collector is a trail that runs through rich orchid habitat. Preferably the trail should decrease in elevation from 3000 to 500 meters over a protracted distance, it should be in a high annual rainfall area with the rain distributed evenly throughout the year, it also should be in a region of extremely high biodiversity and very pronounced local endemism. The adjoining forests, cliffs and embankments would be festooned with the natural epiphytes and terrestrials of the zone. In the Western Hemisphere, prior to the development of roads and highways, such trails from the lowlands to the Andean highlands existed from northwestern Colombia to southern Ecuador and northern Peru and provided the means of communication for people traveling by foot or mule back. Each of those trails might have had more than 1,000 orchid species distributed along their length. Curiously, each trail may have had a very different species’ composition from the next closest trail. The mountains of this region were clothed in mature montane wet forest that appeared to provide very similar conditions from one locality to the next. Yet, careful analysis and comparison of the composition of the orchid flora of several parallel trails reveals a very low commonality of the species. Recent reports suggest that the highest orchid diversity on earth may be in this region. Many collectors visited the zone from the time of Humboldt and Bonpland, C. Mutis, Ruiz & Pavón and Juan Tafalla at the turn of the 18th century. A wave of horticultural collectors were sent out from Europe by the major plant nurseries up through the turn of the 19th century. Most of those collectors were Europe-based and did not remain in the rich regions for prolonged periods of time. Very few actually lived in the orchid-rich regions, partly because those areas were inhospitable climate-wise. By establishing his home near Popayan in southern Colombia, Friederich Carl Lehmann (1850-1903) lived in the midst of those orchid populations, but in quite agreeable climate. He married a local girl, Doña Maria Josefa Mosquera and established a family. He arrived in Colombia about 1876 and collected for about 28 years. That period coincided with the fashion of maintaining large orchid collections by the wealthy of Europe. Lehmann communicated with Professor H.G. Reichenbach f., the leading orchid taxonomist of the time, and after Reichenbach died in 1884, worked with Dr. F. Kraenzlin describing new species of orchids from Colombia and Ecuador. He also sent a large set of his collections to Kew, where many were identified by Robert A. Rolfe. Lehmann travelled by trail and by boat for much of western Colombia and Ecuador, and made a brief plant- collecting trip to Costa Rica and Guatemala. Between 1880 and 1902 he made 7 trips to Ecuador. On those trips he collected live orchids and shipped them to Europe to be sold in the great auction houses such as Hugh Low & Co., Steven’s salesroom and Sanders. The nurseries established the plants and sold them as soon as they flowered at substantial prices. Some were sent home to Popayan where he grew them on to flower. He prepared dry herbarium specimens (collection numbers exceeding 10,000). He also produced paintings of excellent quality of outstanding species. The majority of his paintings have been housed in the orchid herbarium at Kew. Unfortunately, other than for visiting scientists and the staff of Kew, they have not been available to the public. Most have not been published until now. Lehmann’s herbarium specimens were prepared in abundance so that he was able to sell sets to several of the major herbaria of Europe. The orchid specimen collections prepared by Lehmann in the Neotropics over a 25 year period have made a major contribution to the knowledge of the orchids of the region.